Jurisdição constitucional e democracia: uma análise da abstrativização do controle difuso de constitucionalidade - Vello, Renata Pinto Coelho (2011)
Addressed in this study the relation between democracy and constitutional jurisdiction, by examining the phenomenon of abstrativização control of constitutionality and diffuse model analysis of judicial review adopted in Brazil, the hybrid model, examining whether it would be compatible to that with the democratic rule of law. Investigates the consequences of abstrativização the diffuse control of constitutionality to the democratic rule of law and the constitutional effectiveness in view, no longer possible to ignore this phenomenon. The question is answered throughout this work is as follows: the abstrativização contributes to the effectiveness of the Federal Constitution and the democratic rule of law? We analyze therefore the possibility of finding a proper interpretation of the phenomenon of abstrativização diffuse control of constitutionality, which is consistent with the democratic rule of law and contribute to the effectiveness of the Federal Constitution. Thus, it examines the possibility of interpreting the commands of abstrativização diffuse control of constitutionality, the constraint is the following: apply erga omnes effect and binding decisions in the diffuse control of constitutionality that the constitutional issue has been examined only as a cause of action, if the judge finds that the above command is compatible with the peculiarities and arguments raised by those affected in the new case that is being appreciated. This work was divided into three chapters. At first this was the importance of examining the case in a democratic state, in the second, we dealt with the phenomenon of diffuse abstrativização control of constitutionality and the context in which it came, finally, the last chapter are listed the some of the problems arising from abstrativização and it was suggested a new way to interpret it so that it can contribute to the effectiveness of the Federal Constitution and the democratic rule of law.